Exploring the structure of the shot effectiveness model for elite table tennis players - Yang, Q.; Li, M.-Z.; Zhou, Z.; Zhang, H. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Currently, technical and tactical analysis has become an indispensable task for sport in many countries. Many studies analysed players` specific technical and tactical factors, but it is rare to quantitatively analyse the importance of table tennis players` shot effectiveness. This is the first study to propose the new concept of "shot effectiveness model", and the purpose of this study is to explore the structure of the shot effectiveness model for elite table tennis, including the importance degree of shot effectiveness, and the relationship between them.